Detection of some virulence factors of Pseudomonas aeruginosa as a result of treatment with antibiotic Levofloxacin and using specialist primer (Journal of Pharmaceutical Negative Results, 2022)
The current study included a group of (150) clinical swabs for patients suffering from burns, infections in wounds, diabetic foot ulcers and urinary tract infections for both gender, (69) males and (81) females, their ages ranged between 1- 68 years, for the period of November 2021 until the end of February 2022, from Hospitals in Mosul. After the final diagnosis of the samples, (75) isolates of P. aeruginosa were obtained, representing (50%) of the total clinical samples, and the rate of isolation of them from samples of burns, wounds, diabetic foot ulcers and urinary tract infections was 75% (42/56), 41.1% ( 23/56), 53.3% (8/15) and 8.7% (2/23), respectively.The antimicrobial susceptibility test was performed by the disk diffusion method, and it was found that the isolates are multi-antibiotic resistant. The percentage of resistance shown by the isolates were 70.7% for Piperacillin , 89.3% for Amikacin, 74.7% for Aztreonam and Levofloxacin , 81.3% for Gentamicin, Ceftazidime and Cefepime, 76% for Ciprofloxacin, 80% for Netilmicin and Tobramycin , and 45.3% for Imipenem.The effect of the antibiotic Levofloxacin on the PslA gene responsible for the production of biofilms, and the PhzM gene responsible for the production of the pyocyanin pigment by bacteria was studied by extracting the DNA of ten bacterial isolates and then performing a polymerase chain reaction (PCR) using the primers PslA, PhzM, and then performing the electrophoresis process For the final reaction products and to note the presence of Bands before and after the treatment of bacterial isolates with the antibiotic.Five isolates (PA1, PA4, PA5, PA6, PA7) were selected to perform DNA sequencing before and after treatment with the antibiotic Levofloxacin by sending the PCR products of the five samples with the 16SrRNA primer to the Macrogen biotechnology company to know the sequence of nitrogenous bases using a Genetic analyzer 3130 , Changes were observed in the sequence of nitrogenous bases after treatment with the antibiotic Levofloxacin, four new genes were recorded in the National Center for Biotechnology Information (NCBI), and these genes were named short for the name of the supervisor and researcher.